Maturity-associated variation in sport-specific skills of youth soccer players aged 13-15 years - Malina, R. M.; Cumming, S. P.; Kontos, A. P.; Eisenmann, J. C.; Ribeiro, B.; Aroso, J. (Journal of Sports Sciences, 2005)
The aim of this study was to estimate the contribution of experience, body size and maturity status to variation in sport-specific skills of adolescent soccer players. The participants were 69 players aged 13.2 - 15.1 years from three clubs that competed in the highest division for their age group. Height and body mass were measured and stage of pubic hair development was assessed at clinical examination. Years of experience in football was obtained at interview. Six football skill tests were administered: ball control with the body, ball control with the head, dribbling with a pass, dribbling speed, shooting accuracy and passing accuracy. Multiple linear regression analysis was used to estimate the relative contributions of age, stage of sexual maturity, height, body mass and years of formal training in soccer to the six skill tests. Age, experience, body size and stage of puberty contributed significantly but in different combinations to the variance in four of the six skill tests: dribbling with a pass (21%; age, stage of maturity), ball control with the head (14%; stage of maturity, height, body height × body mass interaction), ball control with the body (13%; stage of maturity, years of training) and shooting accuracy (8%; stage of maturity, height; borderline significance, P = 0.06). There were no significant predictors for the tests of dribbling speed and passing accuracy. In conclusion, age, experience, body size and stage of puberty contributed relatively little to variation in performance in four of the six soccer-specific skill tests in adolescent footballers aged 13 - 15 years.